Diseño de sendero agroecoturístico en la granja Santa Inés de la Universidad Técnica de Machala - Guamán Espinoza, Anibal Fidel (2015)
This research involved the design of an agro-ecotourism trial in the farm Santa Inés, Unidad Academica de Ciencias Agropecuarias at the Universidad Técnica de Machala, as the city lacks agro-ecotourism recreational spaces of the same type which do not meet the characteristics and index landscaping necessary, to keep a harmonious relationship with ecology. I identified the different areas that make up the farm Santa Inés with the Geographic Information System. I defined six informative stations which conform the agro-ecotourism path, using GPS, points were taken with their respective coordinates, in each of these, stakes were placed with red paint for later stakeout. The first point was located in the banana plantation with the following coordinates. (Length: 9,636,225 and Latitude: 620,861), the second point was placed in the Botanical Garden with the coordinates (longitude: 9636079 and Latitude: 620,746), the third point was located in the area of Cacao plants, in the outdoor classroom with the following coordinates (length and 9635786 Latitude: 620484), the fourth point was put in the area of Fruit culture, near the gazebo located in this area with the coordinates (length and 9635983 Latitude: 620609) then we placed the fifth point next to the milking module for cattle with the following coordinates (longitude: 9636273 and Latitude: 620,621), finally the sixth and final station was located in the forest with the coordinates (length and 9636553 Latitude: 620711 ) .Finally these points were downloaded into the computer and placed on the map using the AutoCAD software. After processing the data points and locating the six stations in the map, we proceeded to lay out the agro-ecotourist trail digitally with the AutoCAD program, the program also generated the thematic map for the agro-ecotourist path to facilitate the travel of visitors. We estimated the carrying capacity, which is 46 people maximum for the visit of the trail, so the environmental impact according to the cause and effect matrix is moderate